Impact of Culture-Independent Diagnostic Testing on Recovery of Enteric Bacterial Infections. (26th December 2017) - Imdad, Aamer; Retzer, Fiona; Thomas, Linda S; McMillian, Marcy; Garman, Katie; Rebeiro, Peter F; Deppen, Stephen A; Dunn, John R; Woron, Amy M
Abstract : Culture-independent diagnostic test (CIDTs) are increasingly used to diagnose enteric infections; however, public health surveillance of foodborne illnesses has historically depended on isolates. This study found that CIDT-positive specimens yielded a pathogen in only 61% of reported cases compared to culture-derived isolates. Abstract: Background: Culture-independent diagnostic tests (CIDTs) are increasingly used to identify enteric pathogens. However, foodborne illness surveillance systems have relied upon culture confirmation to estimate disease burden and identify outbreaks through molecular subtyping. This study examined the impacts of CIDT and estimated costs for culture verification of Shigella, Salmonella, Shiga toxin–producing Escherichia coli (STEC), and Campylobacter at the Tennessee Department of Health Public Health Laboratory (PHL). Methods: This observational study included laboratory and epidemiological surveillance data collected between years 2013–2016 from patients with the reported enteric illness. We calculated pathogen recovery at PHL based on initial diagnostic test type reported at the clinical laboratory. Adjusted prevalence ratios (PRs) and 95% confidence intervals (CIs) were estimated with modified Poisson regression. Estimates of cost were calculated for pathogen recovery from CIDT-positive specimens compared to recovery from culture-derived isolates. Results: During the study period, PHL received 5553 specimens from clinical laboratories from patients with the enteric illness. Pathogen recovery was 57% (984/1713) from referred CIDT-positive stool specimens and 95% (3662/3840) from culture-derived isolates (PR, 0.61 [95% CI, .56–.66]). Pathogen recovery from CIDT-positive specimens varied based on pathogen type: Salmonella (72%), Shigella (64%), STEC (57%), and Campylobacter (26%). Compared to stool culture–derived isolates, the cost to recover pathogens from 100 CIDT-positive specimens was higher for Shigella (US $6192), Salmonella (US $18373), and STEC (US $27783). Conclusions: Pathogen recovery was low from CIDT-positive specimens for enteric bacteria. This has important implications for the current enteric disease surveillance system, outbreak detection, and costs for public health programs.